Applying a Commercial Determinants of Health Lens to Understand, Expose and Counter Industry Co-option, Appeasement and Partnership; Comment on “‘Part of the Solution’: Food Corporation Strategies for Regulatory Capture and Legitimacy” - Eric Crosbie; Angela Carriedo (International Journal of Health Policy and Management, 2022)
Lacy-Nichols and Williams’ examination of the food industry illustrates how it altered its approach from mostly oppositional to regulation to one of appeasement and co-option. This reflection builds upon this by using a commercial determinants of health (CDoH) lens to understand, expose and counter industry co-option, appeasement and partnership strategies that impact public health. Lessons learned from tobacco reveal how tobacco companies maintained public credibility by recruiting scientists to produce industry biased data, co-opting public health groups, gaining access to policy elites and sitting on important government regulatory bodies. Potential counter solutions to food industry appeasement and co-option include (i) understanding corporate actions of health harming industries, (ii) applying mechanisms to minimize industry engagement, (iii) dissecting industry relationship building, and (iv) exposing the negative effects of public private partnerships (PPPs). Such counter-solutions might help to neutralise harmful industry practices, products and policies which currently threaten to undermine healthy food policies.